Proceedings of Italian Concrete Days 2016 (Lecture Notes in Civil Engineering,, 2018)
This book gathers the best peer-reviewed papers presented at the Italian Concrete Days national conference, held in Rome, Italy, on October 27-28, 2016. The conference topics encompass the aspects of design, execution, rehabilitation and control of concrete structures, with particular reference to theory and modeling, applications and realizations, materials and investigations, technology and construction techniques. The contributions amply demonstrate that today's structural concrete applications concern not only new constructions, but more and more rehabilitation, conservation, strengthening and seismic upgrading of existing premises, and that requirements cover new aspects within the frame of sustainability, including environmental friendliness, durability, adaptability and reuse of works and / or materials. As such the book represents an invaluable, up-to-the-minute tool, providing an essential overview of structural concrete, as well as all new materials with cementitious matrices.